(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Introduction The Argentina Continental Margin (MCA) is one of the largest margins around the world (2x106 km2), which in most of its area of development (between 35 and 48ºS) belongs to a typical extensional volcanic passive margin (Mohriak et al., 2002). The region is located in a key area of the Southwestern Atlantic Ocean due to its significance in the global oceanographic-climatic interaction (Wefer et al., 1996, 2004; Carter and Cortese, 2009). As a result, the study of the Cenozoic sedimentary sequences preserved in the geological record is very important for paleoceanographic-paleoclimatic-paleoenvironmental reconstructions. The study area is included in the northern part of the MCA adjacent to eastern Buenos Aires province (Fig. 1a). The major physiographic units are the shelf, slope, rise and the Mar del Plata Submarine Canyon. This work describes the Cenozoic morphosedimentary, stratigraphic and evolutive aspects of the continental slope in the region. The study is based on high resolution seismic (multi and monochannel) complemented with sediment analysis on piston and gravity cores as well as grab samples (Fig. 1b), obtained during different cruises on board the Research Vessels Puerto Deseado (Argentina) and Meteor (Germany) (Table 1); additional seismic, geological and sedimentological information was gathered from LDEO (USA) and BGR (Germany). Geotectonic, Morphosedimentary and Oceanographic Setting The region (Fig. 1a) is located in the southern part of the Salado basin where post-Cretaceous sediment thickness varies between 2 and 4 kilometers. Stratigraphic information from offshore oil drillings (Fig. 2) indicates that in the outer shelf, immediately west of the study area, sedimentary sequences are represented by Maastrichtian-Paleocene marine deposits, Eocene-Oligocene continental deposits, Miocene marine deposits, Pliocene continental deposits and Quaternary marine deposits (Yrigoyen, 1975, 1999; Tavella and Wright, 1996). These sequences change towards the slope into fully deep-marine facies. Morphosedimentary configuration of the continental slope in the entire passive margin is dominated by a contourite depositional system (Hernández-Molina et al., 2009, Fig. 3a), composed of both depositional and erosive features (drifts, terraces, scarps, submarine canyons) that resulted from complex interactions among sedimentary, oceanographic and climatic components. One of the main conditioning factors is the oceanographic setting (Fig. 3b), characterized by predominance of parallel-to-the-slope (contouritic) south-to-north circulating currents from Antarctic origin, which in the northern part of the margin interact with the North Atlantic water masses, so determining the Confluence Zone. Across-margin sediment transport processes such as turbidity currents are also very significant in the evolution and configuration of the margin. These processes became more important towards the north, particularly in the study area. Morphology and Sedimentology of the Eastern Buenos Aires Province Continental Slope The continental slope in the study area extends between 120 and 3500 m depth (Fig. 4). It is constituted by an upper sector characterized by a steep slope above 700/800 m (upper slope). From there, the middle slope extends seaward, constituting the Ewing Terrace, a terraced, low-gradient feature that extends down to 1300 meters. The lower continental slope has again a steep slope that reaches 3500 m, from where it grades to the continental rise. The continental slope is cut by the Mar del Plata Submarine Canyon that begins at about 500 m depth, showing a typical V-shape configuration between 1200 and 3700 meters. The sedimentary cover in the slope is siliciclastic and consists of sandy muds, which close to the canyon incorporate a higher sand content and pebbles. The mineralogical content belongs to the volcanic-pyroclastic association of pampean-patagonian origin. Figure 5 illustrates a type morphological cross section showing the bottom and near-bottom sediment distribution. Analysis of the forams collected from several cores indicate that in the upper 5 m of the sedimentary cover upper Pliocene to Recent faunas are present, with ages lower than 450 ka at 1.5 m, 120 ka at 0.75 m, and late Holocene in the uppermost 0.5 m. Stratigraphy The seismic-stratigraphic analysis and correlation with geological information from offshore oil drillings allowed to define seven depositional sequences (SD) (named with letters A to G from top to bottom), which encompasses the time-span between Late Cretaceous and the present. They are separated from each other by major seismic reflectors that represent unconformities produced by significant climatic-oceanographic events of regional extension (Tables 2 and 3). Interpretation and correlation among different seismic reflectors defined by several authors (Ewing & Lonardi, 1971, Hinz et al., 1999, Parker et al., 1999, 2005) was needed before defining those that separate the SDs. Figure 6 represents the synthesis of the correlation between seismic and geological information, whereas figure 7 is a type section showing the architecture and regional disposition of the SDs. The depositional sequences are described from bottom (SD G) to top (SD A). SD G: the top of the unit is the seismic reflector AR3 that represents the K-T boundary. The age of the sequence is considered Aptian-Maastrichtian. Internal seismic characteristics are mainly represented by subparallel, semi-transparent reflections. It represents shallow marine environments deposited in a longitudinal basin which evolved as a result of the South Atlantic opening. SD F: Paleocene-upper Eocene. It has a maximum thickness of 900 meters. The internal seismic structure is transparent, with aggrading sequences (Fig. 8a-d) and locally chaotic, sometimes divergent reflections towards the base. Paleovalleys associated to ancient submarine canyons are also evident (Fig. 7). The upper boundary (reflector AR4) shows deep depressions that affect the base of the sequence; this reflector represents a regional expansion of the eastern Antarctic ice masses during Eocene-Oligocene times. The unit represents the final evolution of the "sag" stage in the Salado basin. SD E: upper Eocene-beginning of the mid Miocene. Thickness reaches up to 500 meters. The internal seismic structure shows changing characteristics, with prograding sequences in the base, retrograding sequences in the middle part with wavy megastructures, and aggrading sequences in the upper part with large sediment lobes and paleovalleys (Fig. 8a-d) as well as cut-and-fill structures (Fig. 8d) and debris flows (Fig. 8c). The top reflector (AR5) represents another regional expansion of Antarctic ice masses. The unit shows evidences of deepening of the marine environment from base to top, and seismic reflector R* that divides two lithologically different sections could represent the change from prograding to retrograding facies. SD D: mid to upper Miocene. The top seismic reflector (H2) has a morphology similar to the present surface (Fig. 7). Thickness is about 400 m. Seismic structure is semitransparent, with subparallel reflections and local chaotic configuration. The lower section shows prograding structures indicating the growing of the slope towards the east, whereas the upper section shows retrograding sequences with megawaves (Fig. 8 a-d). A contouritic drift develops in this upper part. Sediment infilling of paleovalleys is also evidenced. The Ewing Terrace is well developed and shows evidence of erosive processes with formation of submarine canyons. SD C: lower Pliocene. Seismic configuration shows morphological features very similar to the present-day topography (Fig. 7). Thickness is less than 200 m. Internal seismic structure is homogeneous, with subparallel seismic reflectors of large lateral extension, prograding structures and channels with internal migrating and filling structures (Fig. 8a-d). In the outer boundary of the Ewing Terrace, retrograding, sometimes chaotic structures are evident. SD B: mid to upper Pliocene. Thickness is less than 200 meters. Internal seismic configuration is of reflectors parallel to top and bottom, with aggrading levels in the upper slope and Ewing Terrace (Fig. 8a-d). SD A: upper Pliocene-Quaternary. Thickness doesn’t exceed few tens of meters. Parallel reflections, turbiditic and contouritic facies as well as slides, debris flows and active erosive-depositional processes are evident. Cores obtained in the upper levels of this unit are composed of muddy and silty sediments with thin sand layers probably representing turbiditic processes. Discussions and Conclusions The sequence stratigraphy, architecture and structures reveals that the continental slope begun to evolve during the Eocene-Oligocene transition as a result of complex processes like aggradation and progradation, with turbiditic-contouritic processes and formation of submarine canyons, mainly associated to oceanographic and climatic conditioning factors. Two main features characterize the slope configuration: the Ewing Terrace and the Mar del Plata Submarine Canyon. The Ewing Terrace mainly resulted from sedimentation conditioned by along-slope, south-to-north flowing contouritic currents with additional strong action of across (down)-slope turbiditic processes. Post-Miocene sequences in the Terrace represent deep marine sedimentary facies genetically associated to sea-level fluctuations. Contouritic deposits seem to be mainly associated to highstands, whereas turbiditic and down-slope slides processes probably dominated during lowstands when high-energy, coastal processes occurred near to the shelf-slope transition. The Mar del Plata Submarine Canyon is an expression of high-energy, turbiditic processes that were probably enhanced during sea-level lowstands (Pickering et al., 1989, Viana et al, 2002, Canals et al., 2006). Intercalations of sandy deposits in between the dominant muddy sedimentation on the terrace around the canyon reveals the importance of turbiditic activity. The configuration of seismic reflector N shows that the canyon reached a morphology similar to the present one in the upper Pliocene. Four stages define the evolution of the study sector of the MCA: 1) Initial aggradational stage, from the Cretaceous to the Eocene, with marked vertical accretion of the slope associated to the "sag" stage with high sedimentation rate in the Salado basin. 2) Growing-up of the slope during upper Eocene-mid Miocene times, when the "passive margin" stage developed and the strong influence of the Antarctic water masses begun to affect the region, what is manifested by the formation of complex sedimentary sequences with alternating prograding-retrograding cycles. Prograding cycles dominate in the region with high turbiditic dynamics and formation of submarine canyons that allowed the seaward advance of the slope. 3) Development of the Ewing Terrace in the mid-upper Miocene, when the sediment dynamics associated to the near-bottom circulation of oceanic currents of Antarctic origin favoured the northward migration of large contouritic deposits. 4) Definitive configuration of the slope in Pliocene-Quaternary times, when the Ewing Terrace and the Mar del Plata Submarine Canyon reached their present characteristics.